مستويات كالسيوم و مغنزيوم المصل في الحمل الطبيعي و الحمل المختلط بما قبل الإرجاج - Hasan, Lowe (Latakia University Journal -Medical Sciences Series, 2019)
مستويات كالسيوم و مغنزيوم المصل في الحمل الطبيعي و الحمل المختلط بما قبل الإرجاج لؤي حسن مقدمة : على الرغم من أنّ الفزيولوجيا المرضية الدقيقة لما قبل الإرجاج غير مفهومةٍ تمامًا ، فقد تمّ اقتراح أنّ العديد من الاضطرابات الشاردية تلعب دوراً في ما قبل الإرجاج . هدف البحث : كان الهدف من هذا البحث هو قياس المستويات المصلية للكالسيوم و المغنزيوم لدى النساء الحوامل المصابات بما قبل الإرجاج و مقارنة النتائج مع الحوامل بحملٍ طبيعيٍّ . المواد و الطرق : قمنا بجمع عينات الدم الوريدية من 35 سيدة حامل مصابة بما قبل الإرجاج و 35 سيدة مع حمل طبيعي . تم تحليل عينات الدم و قياس تركيز الكالسيوم و المغنزيوم باستخدام جهاز تحليل ضوئي (colorimetric) . تم استخدام اختبار ت – ستودنت (Student’s t-test) لتحليل البيانات . النتائج : أظهرت نتائج الدراسة أنّ تركيز الكالسيوم المصلي لدى السيدات الحوامل المصابات بما قبل الإرجاج أخفض بشكل هام إحصائياً منه لدى السيدات مع حملٍ طبيعيٍّ (8.1 ± 0.56 مغ/دل مقابل 9.59 ± 0.62 مغ/دل) ( (P<0.001 . و أنّ تركيز المغنزيوم المصلي لدى السيدات الحوامل المصابات بما قبل الإرجاج أخفض بشكل هام إحصائياً منه لدى السيدات مع حملٍ طبيعيٍّ (1.83 ± 0.21 مغ/دل مقابل 2.03 ± 0.16 مغ/دل) ( (P<0.001. الخلاصة : خلصت دراستنا هذه إلى أنّ كلّاً من المستويات المصلية للكالسيوم و المغنزيوم لدى السيدات الحوامل المصابات بما قبل الإرجاج أخفض بالمقارنة مع السيدات مع حملٍ طبيعيٍّ . تدعم هذه النتائج النظرية التي تقول أنّ نقص كاسيوم الدم و نقص مغنزيوم الدم يلعبان دوراً في سببية ما قبل الإرجاج. Introduction : Although the exact pathophysiology of preeclampsia is not fully understood, several elemental micronutrient abnormalities have been suggested to play a contributory role in preeclampsia. Aim : The aim of this study was to measure serum levels of calcium and magnesium in preeclamptic pregnancies and to compare them with those in normal pregnancies. Materials and Methods : A case-control study was conducted in Tishreen University Hospital, Syria, during the period of September 2016 through September 2017 . The cases were women with preeclampsia while healthy pregnant women were the controls. We collected venous serum samples from 35 preeclamptic pregnant women and 35 normal pregnant women. The blood samples were analyzed for calcium and magnesium, using a colorimetric analyzer. The data were analyzed using the Student’s t-test. Results : The serum calcium concentration in preeclamptic pregnant women was significantly lower than that in normal pregnant women (8.10 ±0.56mg/dl vs 9.59 ±0.62 mg/dl , p<0.001). Serum magnesium concentration in preeclamptic women was significantly lower than that in normal pregnant women (1.83 ± 0.21mg/dl vs. 2.03 ± 0.16 mg/dl , p <0.001). Conclusion : This study shows that both serum calcium and serum magnesium levels in preeclamptic pregnant women are lower than in normal pregnant women. These findings support the hypothesis that hypocalcemia and hypomagnesemia are possible etiologies of preeclampsia.